PENGARUH PEMBELAJARAN BLENDED LEARNING BERBASIS ROTATION MODEL BERBANTUAN MEDIA YOUTUBE TERHADAP KEMAMPUAN BERPIKIR KRITIS DAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA - Indah Resti Ayuni Suri; Bambang Sri Anggoro; Maika Tanzila (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by students’ low critical thinking and mathematical problem-solving skills, which were attributed to teacher-centered learning and the limited use of innovative learning models and engaging instructional media. YouTube as a learning medium supports the implementation of technology-based education. This study aims to determine the effect of Blended Learning based on the Rotation Model assisted by YouTube media on: (1) students’ critical thinking skills, (2) students’ mathematical problem-solving skills, and (3) both abilities simultaneously. This study employed a quantitative approach with a Quasi-Experimental Design. The population consisted of all Grade XI students of SMA Negeri 12 Bandar Lampung in the 2025/2026 academic year, totaling 424 students. The sample was selected using Cluster Random Sampling, with class XI KP 1.1 as the experimental class, which implemented Blended Learning based on the Rotation Model assisted by YouTube media, and class XI KP 1.3 as the control class, which used expository learning. The research instruments were essay tests measuring critical thinking and mathematical problem-solving skills. Data were analyzed using One-Way Multivariate Analysis of Variance (MANOVA). The results showed that Blended Learning based on the Rotation Model assisted by YouTube media had an effect on students’ critical thinking and mathematical problem-solving skills. The first hypothesis obtained a significance value of 0.03, the second hypothesis 0.00, and the third hypothesis 0.01. Thus, the learning model had significant effects on critical thinking skills, mathematical problem-solving skills, and both abilities simultaneously. Therefore, this learning model is effective in improving students’ higher-order thinking skills compared with expository learning.